MARTIKULASI TRIK TENARKAN BAHASA ARAB DI MADRASAH - Novi Ulfa Safitri (Lughoti (Jurnal Pendidikan Bahasa Arab) Jurnal program studi PBA, 2021)
The articulation of Arabic subjects in madrasas is an additional activity given to students with the aim of equalizing understanding of the Arabic language and eliminating gaps in student understanding due to the heterogeneity of student education. This activity at the same time refreshes the materials that have been obtained at the previous education level and can change the negative paradigm of students about learning Arabic which is considered unattractive, difficult to learn, with an allergic, atypical attitude, etc. Because marticulation can be used as an alternative to eliminate the allergic and anti-passive attitude of students towards learning Arabic, with the hope that Arabic can be loved and liked by students. The implementation is at the beginning of the new school year by using the module as a learning resource in the implementation of marticulation to support the achievement of perfect marticulation, with fresh and attractive packaging consisting of; title, goal, strategy / approach, hiwar, game / quiz / test, empty column (test for children's knowledge) and Arabic songs. With the hope that Arabic can be loved, loved and liked by students. Keywords: Marticulation and Arabic